Gambaran Kecemasan Pada Ibu Hamil Trimester Iii Di Puskesmas Pahandut Palangkaraya - Mayang Puspita Candrani Sari; Fitriani Ningsih; Sefentina Agus (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Background Anxiety in third trimester pregnant women in Indonesia reached 28.7%, especially in primigravida mothers. The results of a study in one of the health facility in Palangkaraya city revealed that about 45.5% of pregnant women experienced moderate anxiety. experienced moderate anxiety, while 55.8% of mothers aged 20-35 years showed mild anxiety showed mild anxiety levels. Objective This study aims to determine the anxiety of pregnant women in trimester 3 at the Pahandut Health Center in Palangkaraya. Method This research method uses a research design with a descriptive approach. Descriptive research is a type of research that aims to describe the characteristics of a population or phenomenon without changing or manipulating variables. The results showed that the characteristics of respondents based on age mostly had an age that was not at risk (20-35 years), which amounted to 22 people (85%), the Parity Level of most respondents had the highest parity level of not having children totaling 17 people (65%) and the highest level of employment was mostly not working as many as 21 people (81%). Conclusion of the results of this study shows that the level of anxiety in pregnant women in trimester 3 at the Pahandut Palangkaraya Health Center most of the 15 out of 26 respondents is no anxiety so that the quality of service can improve and be even better.